2015
DOI: 10.1007/s10964-015-0259-3
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Short-Term Longitudinal Associations Between Social Anxiety and Victimization and Perpetration of Traditional Bullying and Cyberbullying

Abstract: Previous research has suggested that social anxiety is associated with victimization and perpetration of (cyber)bullying. The direction and causality of this relationship has not yet been empirically supported for both traditional and cyberbullying involvement. This study examined short-term longitudinal associations between feelings of social anxiety and involvement in traditional bullying and cyberbullying among 2128 adolescents aged 10-17 (56.6 % girls). A cross-lagged panel analysis provided evidence for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
103
4
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(136 citation statements)
references
References 50 publications
15
103
4
14
Order By: Relevance
“…It has been found that individuals mainly use computers, tablet PCs, or mobile telephones to engage in cyberbullying (Hu and Fan, 2013). About 75% of teenagers and 58.4% of college students have indulged in cyberbullying behaviour (Chapin, 2016;Kokkinos et al, 2014), accompanied by certain unhealthy emotions such as depression, social anxiety, and indignation (Pabian and Vandebosch, 2016). In addition, cyberbullying is closely related to some deviant behaviours in real life, such as suicidal behaviour, internet addiction, smoking, and alcoholism (Litwiller and Brausch, 2013;Casas et al, 2013;Pabian and Vandebosch, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that individuals mainly use computers, tablet PCs, or mobile telephones to engage in cyberbullying (Hu and Fan, 2013). About 75% of teenagers and 58.4% of college students have indulged in cyberbullying behaviour (Chapin, 2016;Kokkinos et al, 2014), accompanied by certain unhealthy emotions such as depression, social anxiety, and indignation (Pabian and Vandebosch, 2016). In addition, cyberbullying is closely related to some deviant behaviours in real life, such as suicidal behaviour, internet addiction, smoking, and alcoholism (Litwiller and Brausch, 2013;Casas et al, 2013;Pabian and Vandebosch, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While traditional bullying seems to peak during middle school, cyberbullying peaks somewhat later (Pabian & Vandebosch, 2016). In fact, with age, there seems to be a gradual shift away from traditional forms of bullying such as spreading rumors, to cyberbullying; for example, Mishna, Khoury-Kassabri, Gadalla and Daciuk (2012) found that the older the student, the more likely s/he was to cyberbully others or to both bully and be bullied online, rather than to be a bully or victim.…”
Section: A Typology Of Cyberbullying Actorsmentioning
confidence: 99%
“…For traditional bullying, exposure to such incidences has been associated with anxiety (Stapinksi et al, 2014;Pabian & Vandebosch, 2016), depression and suicidal behaviour (Bauman, Toomey, & Walker, 2013), eating disorders , borderline personality disorder (Wolke, Shreier, Zanarini, & Winsper, 2012), lower self-esteem (O'Moore & Kirkham, 2001) and psychosomatic problems (Fekkes, Pijpers, & Verloove-Vanhorick, 2004). Lower school achievement (Nakamoto & Schwartz, 2010), higher school delinquency (Barboza, 2015) and school dropout (Cornell, Gregory, Huang, & Fan, 2013) are also attributed to victimisation.…”
Section: Consequences Of Bullying and Cyberbullyingmentioning
confidence: 99%